New Insights into Rate Control: Time in Target Range of Resting Heart Rate and Major Adverse Outcomes in Atrial Fibrillation - Yuhui Lai; Xingfeng Xu; Shaozhao Zhang; Rihua Huang; Yiquan Huang; Xiangbin Zhong; Zhenyu Xiong; Yifen Lin; Huimin Zhou; Yue Guo; Xinxue Liao; Yuedong Ma; et al. (Ubiquity Press, 2024)
Background: Few studies have examined the relationship between the fluctuation of heart rate control over time and cardiovascular outcomes in patients with atrial fibrillation. Our study sought to evaluate the independent association between time in target range (TIR) of resting heart rate and cardiovascular outcomes in the AFFIRM (Atrial Fibrillation Follow-Up Investigation of Rhythm Management) study. Methods: Target range of resting heart was defined as less than 80 beats per minute (bpm) for both rate and rhythm control groups. Time in target range was estimated over the first 8 months of follow-up using Rosendaal interpolation method. The association between TIR of resting heart rate and cardiovascular outcomes was estimated using adjusted Cox proportional hazards regression models. Results: Time in target range of resting heart rate (months 0 through 8) was 71 ± 34% in the rate control group and 83 ± 27% in the rhythm control group. Each 1-SD increase in TIR of resting heart rate was significantly associated with lower risk of major adverse cardiovascular events after full adjustment for demographics, medical history and history of prior heart surgery, as well as all-cause mortality. Conclusions: Time in target range of resting heart rate independently predicts the risk of cardiovascular outcomes in patients with atrial fibrillation. Long-term maintenance of heart rate on target is of great importance for patients with atrial fibrillation.